2017
DOI: 10.25077/jpi.19.1.23-29.2017
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pemberian Pakan dengan Sumber Protein Berbeda terhadap Persentase Potongan Karkas dan Massa Protein Daging Ayam Lokal Persilangan

Abstract: ABSTRAKTujuan dari penelitian ini adalah mengetahui pengaruh pemberian pakan dengan sumber protein berbeda terhadap persentase potongan karkas dan massa protein daging ayam lokal persilangan. Materi yang digunakan adalah 126 ekor ayam lokal persilangan (unsexed) umur2 minggu dengan bobot badan 129 ± 6,34 g. Bahan pakan yang digunakan yaitu jagung, bekatul, bungkil kedelai, tepung ikan, MBM (Meat bone meal) dan PMM (Poultry meat meal). Rancangan percobaan yang digunakan adalah RAL (Rancangan acak lengkap) denga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Waly et al (2021) added that better absorption of nutrients has a positive effect on the level of digestibility. Digestibility is closely related to feed consumption, where livestock that have a higher consumption rate may hoard more protein as a form of growth response that is useful for carcass formation (Pratiwi et al, 2017).…”
Section: Results and Discussion Overview Of The Research Locationmentioning
confidence: 99%
“…Waly et al (2021) added that better absorption of nutrients has a positive effect on the level of digestibility. Digestibility is closely related to feed consumption, where livestock that have a higher consumption rate may hoard more protein as a form of growth response that is useful for carcass formation (Pratiwi et al, 2017).…”
Section: Results and Discussion Overview Of The Research Locationmentioning
confidence: 99%
“…Then the results of this study were higher than the results of research from [17] which showed the value of protein consumption in native chickens reared for 10 weeks from the age of 0 -10 weeks ranged from 23.17 -35.77 (grams/head/week), and the results of research by [14] which where the value of protein consumption of native chickens reared for 10 weeks (age 10 -20 weeks) ranged from 56.28 -79.38 (grams/head/week). High protein consumption is also followed by high protein intake, which results in higher protein to be used in the formation of meat for livestock [18].…”
Section: Crude Protein Consumptionmentioning
confidence: 99%
“…Therefore, the government issued a ban on the use of antibiotics as Agent Growth Prometer or AGP to boost the growth of poultry livestock which has been regulated in Law No. 18 Therefore, it is necessary to find feed additives or feed additives that have active compounds in naturally promoting growth and improving performance in native chickens. One of the feeds that has active compounds in it is the marine fungus Nodulisporium sp.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely to cause a tendency to increase the cutting weight. The protein content in the ration is used for tissue growth and production and is part of the enzyme structure, so that protein is known as one of the main constituents of body cells and tissues [18].…”
Section: Slaughter Weightmentioning
confidence: 99%